(untitled) (Journal of Atomic and Molecular Sciences, 2013)
The electronic structure and optical properties of the perovskite oxide LaAlO_3, SrTiO_3 and LaAlO_3 /SrTiO_3 interfaces were studied by the density functional theory (DFT) based on First-principles plane wave pseudopotential method. The energy band structure analysis shows that the (AlO_2)^-/(TiO_2)^0 interface is insulating with the band gap being 1.888 eV, whereas the (LaO)^+/(SrO)^0 interface seems to be a semiconductor or semimetal with the band gap being 0.021 eV. Moreover, we have also investigated optical properties of the LaAlO_3, SrTiO_3 and LaAlO_3/SrTiO_3 interfaces, the results indicate that the intensities of absorption, reflectivity, and energy loss spectra of LaAlO_3 and SrTiO_3 are higher than the corresponding intensities of the LaAlO_3 /SrTiO_3 interfaces.